Uma análise da tradução de marcadores culturais em Kafka à beira-mar e Kafka on the Shore, à luz dos estudos da tradução baseados em corpus - kawashita , Kamyla katsue (2017)
The aim of this study is to investigate cultural markers (MCs) in Umibe no Kafuka (2002), by the Japanese writer Haruki Murakami, and to analyze their respective translation in Kafka à beira-mar (2008) by Leiko Gotoda, and Kafka on the Shore (2005), by James Philip Gabriel, referred in this study as TO, TTp and TTi, respectively. We intended to study the choices made by the translators of the target texts when faced with cultural differences in order to observe similarities and differences in both texts. To accomplish so, we investigated translation modalities and features of explicitation, simplification and normalization found in the translation of the MCs. The theoretical and methodological approach consist in Camargo’s interdisciplinary proposal (2004, 2007), which is grounded on Corpus-Based Translation Studies (Baker, 1993, 1995, 1996, 2000), on Baker’s study on translation features (1996), and on Corpus Linguistics (Berber Sardinha, 2004). It also adopts the use of electronic tools provided by the computer software WordSmith Tools for investigating the corpus and analyzing the data. For the study of the MCs, we selected the works on cultural domains (Nida, 1945) and its reformulation (Aubert, 1981, 2006), and the study on translation modalities (Aubert, 1984, 1998). The results show significant keyness for the MCs jinja/shrine (185,20), futon (112,79), udon (82,56) and pachinko (54,00) in TTi, and jinja/santuário (172,49) and ikiyou (70,80) in TTp. Adaptation and Calque are the most representative translation modalities found in the translation of the MCs. We also identified greater features of explicitation in TTp, and simplification and normalization in TTi.